Is endovascular treatment of aorto-iliac aneurysms with simultaneous unilateral revascularization of internal iliac artery by branched iliac stentgraft sufficient? - Drac, Petr; Cerna, Marie; Kocher, Martin; Utikal, Petr; Thomas, Rohit Philip (Biomedical papers, 2021)
Aims. The coverage / occlusion of internal iliac artery (IIA) during endovascular treatment of aorto-iliac aneurysms (AIA) can be associated with risk of ischemic complications. To reduce these complications, unilateral or bilateral iliac branch device implantation (IBDI) has been reported. This study aims at evaluating the efficacy of simultaneous unilateral IBDI in the treatment of AIAs and comparing our results with literature.Materials and Methods. From March 2010 to December 2019, 27 patients (25 men, 2 women, range 54-84 years) were treated for aorto-iliac/isolated common iliac aneurysms with simultaneous unilateral revascularization of IIA and surgical / endovascular occlusion of contralateral IIA. 27 iliac-branched devices were implanted in 27 patients. The results including ischemic complications were evaluated and compared with literature. Results. The technical success was 100% with no perioperative mortality and morbidity of 3.7%. Primary internal iliac branch patency at a median follow-up of 52 months (range 1-118 months) was 96.42%. Secondary endoleak was observed in 6 patients (Type 1a [1], Type 1b [1], Type II [4]) and inflammatory complication in 1 patient. The incidence of buttock claudication one year after the procedure was 11.1%. Except for buttock claudication no other ischemic complications occurred. Conclusion. Unilateral flow preservation in the IIA territory using IBDI is associated with a lesser, but a certain risk of ischemic complications. Bilateral IBDI with bilateral flow preservation of IIAs increases the complexity, procedure -/ fluoroscopy times, contrast agent volume and cost, however, may further reduce these ischemic complications.
Keywords: bilateral aorto-iliac aneurysm; bilateral isolated common iliac aneurysms; endovascular treatment; iliac-branched device; internal iliac artery